IN-PATIENTS’ SATISFACTION LEVEL TOWARDS NURSING CARE SERVICES AND ASSOCIATED FACTORS AT PUBLIC HOSPITALS OF ADDIS ABABA, ETHIOPIA - Tsegaw, Melsew Getinet (Journal of Health, Medicine and Nursing, 2017)
Objective: This study was aimed at assessing the level of patient satisfaction and associated factors among patients towards nursing care services at public hospitals of Addis Ababa. Methods: The statistical protocol of the project was a cross-sectional study undertaken at six public hospitals governed under Addis Ababa Administration Health Bureau. A total of 422 In-patients participated. Participants were selected and included in to the study prospectively and based on availability on discharge during the specified data collection period until the required sample size was reached. Participants were interviewed using a modified structured Amharic version of the New Castle Nursing Satisfaction Scale tool. Data entry was made using EPI-info and analysis was carried out using SPSS 20 software. The primary method of statistical analysis was logistic regression. Result: The study revealed a 48.8 % of overall satisfaction rate of patients towards nursing care services. Age category of 18-40 (P-value=0.001), a monthly income level of Birr < 1000 (P-value=0.02) and <Birr 2500 (P-value = 0.01), patients admitted in medical ward (P-value=0.012), and surgical ward (P-value=0.003), previous admission history (P-value=0.01), length of hospital stay > 30 days (P-value=0.001), co-morbidity (P-value=0.001) and unavailability of particular assigned nurse were significant predictors of dissatisfaction with the nursing care services. Those with educational level of secondary (P-value=0.001) and tertiary (P-value=0.001) were more likely to be satisfied with the nursing care services rendered to them. Conclusion and Recommendation: A relatively low level of satisfaction towards nursing care services was revealed. Old age, a better monthly income and advanced education were the most significant demographic predictors of satisfaction with nursing care services. Those with previous admission history, stayed longer, who had co-morbidity and unavailability of specific assigned nurse were significant predisposing factors of dissatisfaction. On job training for nurses, standing use of contextualized and validated assessment tools to evaluate the patients' perceived satisfaction are important.